2020
DOI: 10.3390/antibiotics9100673
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Antibiotic Resistance Profiles in Methicillin-Sensitive S. aureus Pathotypes Isolated on a Commercial Rabbit Farm in Italy

Abstract: The breeding of meat rabbits is an important sector in the livestock industry in Italy. The focus of this study was to describe the antibiotic resistance profile distribution among the Methicillin-sensitive Staphylococcus aureus isolated in a rabbit farm. From 400 animals of different ages and three farm workers, 96 randomly selected strains isolated from various anatomical sites and lesions were analysed. According to spa typing and the resistance profiles towards veterinary and human antibiotics, 26 pathotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
3
10
1
Order By: Relevance
“…In this study, none of the S. aureus harbored the mecA gene, indicating the absence of MRSA. The finding agrees with the study of Attili et al [ 3 ], which reported a 0% MRSA prevalence rate among live rabbits from Italy. However, another previous study reported MRSA among rabbit handlers and rabbits, with the prevalence rate recorded at 32% and 3%, respectively [ 2 ].…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…In this study, none of the S. aureus harbored the mecA gene, indicating the absence of MRSA. The finding agrees with the study of Attili et al [ 3 ], which reported a 0% MRSA prevalence rate among live rabbits from Italy. However, another previous study reported MRSA among rabbit handlers and rabbits, with the prevalence rate recorded at 32% and 3%, respectively [ 2 ].…”
Section: Resultssupporting
confidence: 93%
“…A similar result was also reported by Wang et al [ 14 ], where the antibiotic-resistance rates of S. aureus against penicillin (11%), kanamycin (19.6%), gentamicin (10%), and ciprofloxacin (3.9%) were less than 20%. However, a previous study conducted in Italy reported that most of the S. aureus isolated from rabbits were highly resistant against tetracyclines (96%) and macrolides (94%) [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations